Patterns and predictors of mortality in the first 24 hours of admission among children aged 1-59 months admitted at a Regional Referral Hospital in South Western Uganda. - Moses Ochora; Stella Kyoyagala; Lydia Kyasimire; Mercy Akambasisa; Margaret Twine; Muna Ahmed; Dan Lutasingwa; Dorah Nampijja; Elias Kumbakumba (PLoS ONE)
Most deaths among children under 5 years occur within the first 24 hours of hospital admission from preventable causes such as diarrhea, pneumonia, malaria, and HIV/AIDS. The predictors of these deaths are not yet well documented in our setting. This study aimed to describe the patterns and predictors of these mortalities among children aged 1-59 months at a regional hospital in South Western Uganda. We conducted a prospective cohort study among 208 children aged 1-59 months admitted to Mbarara Regional Referral Hospital. The mortality rate within the first 24 hours was 7.7% (95% CI 4-12) and the median time to death was 7.3(2.62-8.75) hours. Most deaths occurred in infants, with severe pneumonia, severe acute malnutrition, and malaria as leading causes. Factors predicting mortality included admission during the night (AHR: 3.7, 95% CI 1.02-13.53, p-value 0.047) and abnormal neutrophil count(AHR: 3.5, 95% CI 1.10-11.31, p-value 0.034). The study highlights the importance of timely interventions, particularly for infants, and suggests extra monitoring for those admitted at night or with abnormal neutrophil counts.